2011
DOI: 10.1117/12.879716
|View full text |Cite
|
Sign up to set email alerts
|

HiPER laser: from capsule design to the laser reference design

Abstract: HiPER (High Power laser Energy Research) is the first European plan for international cooperation in developing inertial fusion energy. ICF activities are ongoing in a number of nations and the first ignition experiments are underway at the National Ignition Facility (NIF) in the USA. Although HiPER is still in the preparatory phase, it is appropriate for Europe to commence planning for future inertial fusion activities that leverage the demonstration of ignition. In this paper we shall detail some of the key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
6
0
3
Order By: Relevance
“…Included in the design as a mandatory requirement is the use of a phase plate to both condition the focal spot and create the necessary stationary speckle pattern. This bundle design has many advantages when considering focal spot conditioning, optical zooming, and pulse shaping; it has been described in detail in [22][23][24] . Both NIF and LMJ have shown that in solid-state lasers, the bandwidth is large enough to withstand phase modulation as a necessary requirement for beam smoothing and stimulated Brilloouin scattering (SBS) suppression.…”
Section: Laser Design: Architecturementioning
confidence: 99%
See 2 more Smart Citations
“…Included in the design as a mandatory requirement is the use of a phase plate to both condition the focal spot and create the necessary stationary speckle pattern. This bundle design has many advantages when considering focal spot conditioning, optical zooming, and pulse shaping; it has been described in detail in [22][23][24] . Both NIF and LMJ have shown that in solid-state lasers, the bandwidth is large enough to withstand phase modulation as a necessary requirement for beam smoothing and stimulated Brilloouin scattering (SBS) suppression.…”
Section: Laser Design: Architecturementioning
confidence: 99%
“…In both cases, the compression pulse is preceded by an adiabatic shaping picket (of 100–200 ps duration) from Ref. [22]. The times of the initial shocks are in the nanosecond regime whilst the final rise of the pulse can be 100 ps.…”
Section: Laser Design: Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7][8][9] La composición y estructura de las cámaras de los futuros reactores de fusión láser está todavía en proceso de desarrollo; no obstante, se han elaborado varios esquemas para algunos de los reactores de investigación, como el representado en la Figura 1.1, para el proyecto HiPER (proyecto europeo de fusión láser. 1,10 En este proyecto se ha propuesto una cámara esférica de 6.5 metros de radio interno en el que se incidirá sobre el blanco con 48 haces láser colocados simétricamente y ópticas finales basadas en lentes de transmisión biconvexas situadas a 16 m del centro con dimensiones de 75 × 75 cm 2 , siendo visible un cuadrado de 60 cm de lado. 1,10,11 Otros esquemas plantean distintas posiciones y tamaños de lentes, como el caso de LIFE 12 que propone usar lentes de Fresnel situadas a 17 m y con unas dimensiones de 48 × 48 cm 2 .…”
Section: Motivación Y Estado Del Arteunclassified
“…1,10 En este proyecto se ha propuesto una cámara esférica de 6.5 metros de radio interno en el que se incidirá sobre el blanco con 48 haces láser colocados simétricamente y ópticas finales basadas en lentes de transmisión biconvexas situadas a 16 m del centro con dimensiones de 75 × 75 cm 2 , siendo visible un cuadrado de 60 cm de lado. 1,10,11 Otros esquemas plantean distintas posiciones y tamaños de lentes, como el caso de LIFE 12 que propone usar lentes de Fresnel situadas a 17 m y con unas dimensiones de 48 × 48 cm 2 . En fusión láser se emplean dos métodos de iluminación, directa (p.ej.…”
Section: Motivación Y Estado Del Arteunclassified